Pengaruh Kinerja Keuangan Terhadap Interest Coverage Ratio (ICR) pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2020 di Masa Pandemi Covid-19 - Pangestu, Angelia Yoga; Andre Bustari (Fakultas Ekonomi, Universitas Ekasakti, 2023)
This study aims to analyze the effect of financial performance on the Interest Coverage Ratio (ICR) of manufacturing companies listed on the Indonesia Stock Exchange in 2020 during the covid-19 pandemic. The financial performance consists of: Profitability, activity, liquidity and leverage. This type of research uses a quantitative with a descriptive approach. The population in this study were 190 manufacturing companies listed on the Indonesia Stock Exchange in 2020. Using the purposive sampling method, 58 samples of manufacturing companies were obtained. Data analysis used classical assumption test, multiple determination coefficient analysis (R2), multiple linear regression analysis, t test (partial) and F test (simultaneous). The results of the study found that profitability had an insignificant positive effect on Interest Coverage Ratio (ICR), activity had a significant positive effect on Interest Coverage Ratio (ICR), liquidity had an insignificant positive effect on Interest Coverage Ratio (ICR), leverage had an insignificant negative effect on Interest Coverage Ratio (ICR), while profitability, activity, liquidity and leverage have a significant positive effect simultaneously on Interest Coverage Ratio (ICR).